LEGAL REVIEW FOR PERPETRATORS OF THE CRIMINAL ACTS OF EXPLOITATION OF HUMAN TRAFFICKING BASED ON THE TPPO LAW (Study of Case Decision Number: 2400/Pid.Sus/2023/Pn.Mdn) - Ganda Permana Ketaren; Chairuni Nasution; Yasmirah Mandasari Saragih (CV. RADJA PUBLIKA, 2025)
In Indonesia, since the beginning of independence, the government has created the 1945 Constitution which includes protection for all Indonesian people and provides welfare for its citizens. The problem of